1973
DOI: 10.1017/s0021859600058937
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sowing date and season on growth and yield of oilseed rape (Brassica napus)

Abstract: SummaryExperiments made between 1967 and 1970 tested the effects of sowing oilseed rape on different dates in autumn and spring. Much greater oil yields were obtained from autumn sowings, due to higher seed yields and oil content, but the effect varied considerably between experiments, varieties and seasons. Autumn-sown crops flowered in late April or early May, and by the time pods were developing rapidly in June the leaves had senesced almost completely. Spring-sown varieties followed a similar pattern but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 4 publications
4
29
1
Order By: Relevance
“…Due to varying sowing methods and autumn N supplies, 16 different WOSR canopies were established in autumn, each combined with increasing spring N fertilization in order to estimate N response curves separately for each canopy. The results confirmed the current recommendation that under the climatic conditions of northern Europe WOSR should ideally be sown between the middle and end of August, whereas plant establishment after mid-September clearly decreased seed yield, which was in agreement with [7]. It should be noted that, if the weather conditions in the following spring are favorable, even an WOSR crop sown in the third week of September with two to four leaves at the end of autumn growth was able to achieve more than 5 t·ha −1 [29]; however, since long-term weather forecasts are not yet available, the risk of yield penalties increases with shifting WOSR sowing to the end of September.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Due to varying sowing methods and autumn N supplies, 16 different WOSR canopies were established in autumn, each combined with increasing spring N fertilization in order to estimate N response curves separately for each canopy. The results confirmed the current recommendation that under the climatic conditions of northern Europe WOSR should ideally be sown between the middle and end of August, whereas plant establishment after mid-September clearly decreased seed yield, which was in agreement with [7]. It should be noted that, if the weather conditions in the following spring are favorable, even an WOSR crop sown in the third week of September with two to four leaves at the end of autumn growth was able to achieve more than 5 t·ha −1 [29]; however, since long-term weather forecasts are not yet available, the risk of yield penalties increases with shifting WOSR sowing to the end of September.…”
Section: Discussionsupporting
confidence: 90%
“…While Luteman and Dixon [1] found only small yield penalties, Uzan et al [6] reported a decline in seed yield of canola cultivars with a delay in sowing date under Mediterranean environment conditions due to shortening the length of the reproductive period and consequently the potential grain-filling period. Also, Scott et al [7] showed large yield penalties if sowing occurred after mid-September.…”
Section: Introductionmentioning
confidence: 99%
“…Assimilate production by a rapeseed crop is greatly dependent on leaf area index which, in tum, is highly responsive to increased nitrogen supply to the plant (Scott et al 1973). Increasing levels of nitrogen supply will therefore result in larger plants producing more pods and higher seed yield.…”
Section: Carbon/nitrogen Metabolismmentioning
confidence: 99%
“…Leaves rapidly senesce after flowering in a sequential manner starting with the lowest remaining leaf. Scott et al (1973) concluded that by the time the sununer rape crop was in flower, the leaves had largely fulfilled their role in plant development and provided they were allowed to retranslocate mobile nutrients, their loss as a photosynthetic surface was not significant.…”
mentioning
confidence: 99%